Um panorama do trabalho remoto no Brasil e nos estados brasileiros durante a pandemia da Covid-19 - Geraldo Sandoval Góes; Felipe dos Santos Martins; José Antônio Sena Nascimento (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This study investigates the potential and effective remote work in Brazil in 2020. Using information from the Continuous PNAD and methodology developed in the international literature and adapted for the country, the potential of occupations that can be carried out remotely is estimated. Added to this, based on the PNAD Covid-19 for different months, a portrait of the profile of the person effectively exercising their labor activity is constructed remotely due to the covid-19 pandemic in Brazil. Furthermore, a model is estimated identifying the main components correlated to home office. The results show that although about a fifth of the workers are in occupations that can be performed remotely, just over 10% actually worked remotely. Finally, the study points out that education is the individual variable most correlated with the probability of remote work in the country.
Keywords: J01; J19; J81; 330; home office; labor market; covid-19 pandemic